Homogeneização biótica em metacomunidades heterogêneas de fitoplâncton impactadas por agroquímicos - Santos, Ana Carolina dos (Universidade Federal de São Carlos, 2022)
Agrochemicals are largely used in sugar cane production in Brazil and they contaminate water bodies and potentially they can cause a process named biotic homogenization, through species selection and changes in the aquatic species compositions. In metacommunities the contamination can affect uncontaminated and connected water bodies through organisms dispersion or effluents sharing, on the other hand we can also predict that non affected places can help the local communities to recover after agrochemicals exposure directly, acting as key-communities and that phytoplankton communities would suffer the biotic homogenization process through pesticides (e.g., fipronil) and fertilizers (e.g., vinasse) addiction. The first one would cause top-down remotion, because of its toxicity to zooplankton and the second one would cause it because of bottom-up remotion by nutrients increase, leading to eutrophication. In contrast, fertilizers could also promote biotic heterogenization as a result of resources increase, which can favour a greater quantity of species. In this study, tried to understand possible changes in phytoplankton special and temporal composition in presence of fipronil and sugarcane vinasse, separately and test how key-communities can help contaminated communities to recover. To test our four hypotheses, we conducted an experiment in mesocosms outdoor contaminated with realistic concentrations for water bodies (an average of 2 µg/L of fipronil and 125 mL of vinasse for each 400 L mesocosm), considering a metacommunities approach, with dispersion among mesocosms. We found that the presence of the contaminants enhanced the diversity and richness loss, although it increased the species evenness. We also observed changes in the species composition, in which the same species respond to the top-down and bottom-up controls loosening or removal, respectively. Pesticides and fertilizers, in the concentrations we tested, tend to lead the phytoplankton communities to beta diversity decrease, although subsequently, the communities were able to recover, which does not support the biotic homogenization hypothesis. The species with the major contributions to beta diversity are the same for both contaminants and the patterns for local contributions were not clear, but it suggested that pristine communities had negative impacts after they received effluents and organisms from impacted locals. We concluded that the presence of contaminants in the current concentrations that are found in aquatic ecosystems can cause beta diversity decrease to phytoplankton communities that can still be recovered and that it selects species with some similar and particular characteristics in both cases, but mainly, that negative effects also occur on nonaffected communities that receive effluents and organisms from affected ones.
Biotic homogenization of heterogeneous phytoplankton metacommunity impacted by agrochemicals
Keywords: Homogeneização biótica; Diversidade beta; Fipronil; Vinhaça; Mesocosmos; Fitoplâncton; Biotic homogenization; Beta diversity; Fipronil; Vinasse; Mesocosms; Phytoplankton; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS